Body Mass Index and Risk of Prostate Volume, International Prostate Symptom Score, Maximum Urinary Flow Rate, and Post-Void Residual in Benign Prostatic Hyperplasia Patients. Issue 4 (August 2019) - Li, Bing-Hui; Deng, Tong; Huang, Qiao; Zi, Hao; Weng, Hong; Zeng, Xian-Tao
The objective of this study was to evaluate association between body mass index (BMI) and prostate volume (PV), international prostate symptom scores (IPSS), maximum urinary flow rate ( Q max ), and post-void residual (PVR) of Chinese benign prostatic hyperplasia (BPH) patients. All newly diagnosed BPH patients between September 2016 and August 2018 were selected and 788 patients were included. According to BMI, the patients were categorized into four groups, while according to PV, IPSS, Q max, and PVR, they were categorized into two groups based on clinical significant cutoffs. Univariable and multivariable logistic regressions and a restricted cubic spline (RCS) were applied to explore the relationship of BMI with categorical PV, IPSS, Q max, and PVR. Compared with normal BMI, obesity presented significant association with increased risk of larger PV (>80 ml) in both unadjusted and adjusted models (unadjusted odds ratio [OR] = 1.772, 95% CI [1.201, 2.614], p = .004; adjusted OR = 1.912, 95% CI [1.212, 3.017], p = .005); however, underweight or overweight did not present a significant connection with such risk. No significant effect was identified for BMI on IPSS, Q max, or PVR in either unadjusted or adjusted model. Nonlinear test including BMI using RCS and adjusting for confounders showed no significance ( p > .05); however, a significant linear relationship was ascertained between BMI and the risk of larger PV ( p < .001). In conclusion, there was a significant linear association between BMI and the risk of larger PV in BPH patients. Hence, this suggests urologists should consider both BMI and PV when providing surgical treatment for BPH patients.